Transitional experiences of Australian health science researchers: where is academic teaching preparedness? - Lamon, Séverine; Knowles, Olivia; Currey, Judy (Frontiers in Education, 2024)
Academic career development relies on a combination of teaching and research skills. In Australia, it is common for recent Doctor of Philosophy graduates to have a short-term post-doctoral research experience to build publication track-record and increase grant competitiveness, before securing a combined research and teaching or ‘academic’ role at a university. Other scientists work as full-time researchers for several years before transitioning to academic roles with expectations they can teach. The aim of this study was to explore the experiences of health and biomedical science researchers transitioning into academic roles using a mixed methods design. Sixty-six participants working in health and biomedical sciences at over 20 Australian Universities who had been in an academic role for five years or less completed an online survey. Of 66 participants, 18 (27%) had never been in a research-only role before, while 48 (63%) had held a research-only role for up to 11 years before starting their current academic role. Findings showed most academics were not trained nor equipped to successfully undertake scholarly teaching. They reported a lack of awareness of teaching expectations, practical resources, and direct support provision at the start of their appointment. For former researchers specifically, these experiences led to low confidence and poor enjoyment in their academic role, with the potential to decrease overall teaching quality, student learning and student satisfaction. We postulate that these issues may be mitigated by the implementation of teaching-specific training programs catering for the research-only background of staff entering health and biomedical academic roles in the higher education workforce.